Lipid Droplets in Neurodegenerative Disorders - Farmer, Brandon C.; Walsh, Adeline E.; Kluemper, Jude C.; Johnson, Lance A. (Frontiers in Neuroscience, 2020)
Lipid droplets have been long regarded as simple storage depots of intracellular neutral lipid. However, recent studies have informed significant roles for lipid droplets in cellular signaling, metabolic disease, pathophysiology, and inflammation. While lipid droplet biology has been well-explored in the periphery, lipid droplets within the brain are relatively understudied. The presence and function of these dynamic organelles in the central nervous system has recently gained much more attention, especially in the context of neurodegeneration. In this review, we seek to summarize the current understanding of lipid droplets within the brain, with an emphasis on their relevance in neurodegenerative diseases. We hope to update investigators in an effort to open new avenues of investigation into this under-appreciated organelle.